Fruit Pulp and Beverage Industry of Gujarat : A Technical Case Study - Modi, Ramesh B.; Patel, Komal N. (AMC Indian Journal of Entrepreneurship, 2018)
The food industry in India is growing at a fast pace.The agro processing units are the major contributors of the food industry. This paper covers the technical survey of the fruit pulp and beverage processing industry in Gujarat, India. The season and the type of fruits being processed to manufacture pulp and beverages are also surveyed and presented in the data. The data presented in this paper shows the region wise presence of industry, scale of operation of the industry, manpower, and employment information in the industries, and the type of constrains the industry is facing.